Influence of transition metal doping (Fe, Co, Ni and Cr) on magnetic and magnetocaloric properties of Pr0.7Ca0.3MnO3 manganites. Issue 8 (September 2015) - Selmi, A.; M'nassri, R.; Cheikhrouhou-Koubaa, W.; Chniba Boudjada, N.; Cheikhrouhou, A.
Abstract: We have studied the influence of the transition metal doping on magnetic and magnetocaloric properties in a polycrystalline sample of Pr0.7 Ca0.3 MnO3 prepared by solid-state reaction. Structural studies show that our samples are single phase and crystallize in the distorted orthorhombic system with Pnma space group. The measurements of the temperature and field dependences of the magnetization clearly show that the Pr0.7 Ca0.3 Mn0.9 A0.1 O3 (A=Cr, Ni, Co and Fe) ceramics exhibit a paramagnetic–ferromagnetic transition with decreasing temperature. The Arrott plots of ours materials reveal the occurrence of a second-order phase transition. Samples partly substituted at the Mn site by 10 at% of Cr, Ni, Co and Fe drive the system from charge order state to ferromagnetic one with a Curie temperature equal to ~80 K, ~116 K, ~118 K, and ~150 K for A=Fe, Co, Ni and Cr respectively. The maximum magnetic entropy changes of the samples doped with Cr, Ni, Co and Fe respectively for a field change of 5 T were found to be 2.37, 2.94, 3.2 and 2.1 J/kg K. The associated RCP values are respectively 222.78, 308.7, 300.8 and 183.5 J kg −1 . These values can be considered as promising materials in magnetic refrigeration technology.